FEATURES OF PERSONNEL MANAGEMENT IN INTERNATIONAL COMPANIES - Tarnovska, Iryna (Collection of scientific papers «ΛΌГOΣ», 2022)
Personnel management in international companies is a special type of management activity, a set of principles, norms and methods of management of an international team of organizations operating on a global scale. Personnel management in international companies is characterized by such features as: cultural factors and ethical issues that affect the actions of personnel of an international firm; different human resource management practices in different branches; differences in labor markets in different countries; the need to move employees between divisions of the company located in different countries; relations between workers, trade unions and entrepreneurs; national orientation of staff and complexity of performance monitoring